Factor influencing the survivability of Tetragenococcus halophilus CH6-2 in the spray drying process - Trung Thanh, Nguyen; Oanh, Vu Thi Kieu; Ha, Le Thanh (Vietnam Journal of Science and Technology, 2023)
In this study, several factors affecting Tetragenococcus halophilus CH6-2 cell survival rate in spray drying process including growth conditions, protective agents, and stress adaption were investigated. T. halophilus CH6-2, which was grown in different media, was mixed with different protective agents or at different ratios of cell concentration to protective agents or was subjected to stress adaption before spray drying. The survival rate after spray drying and after storage was determined. The results showed that skim milk had the strongest protective effect on T. halophilus CH6-2 cells during spray drying. De Man, Rogosa and Sharpe (MRS) was a better medium than our developed M7 optimal medium for culturing T. halophilus CH6-2 in respect of survivability after storage. Increasing the cell/protective agent ratio from 1/20 to 1/3 could increase the survivability after spray drying but not during storage. The heat stress and osmotic stress in this study did not improve the cell survivability after spray drying and storage.